2017
DOI: 10.1186/s13053-017-0078-5
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer incidence in path_MLH1 carriers subjected to different follow-up protocols: a Prospective Lynch Syndrome Database report

Abstract: BackgroundWe have previously reported a high incidence of colorectal cancer (CRC) in carriers of pathogenic MLH1 variants (path_MLH1) despite follow-up with colonoscopy including polypectomy.MethodsThe cohort included Finnish carriers enrolled in 3-yearly colonoscopy (n = 505; 4625 observation years) and carriers from other countries enrolled in colonoscopy 2-yearly or more frequently (n = 439; 3299 observation years). We examined whether the longer interval between colonoscopies in Finland could explain the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 27 publications
6
47
1
Order By: Relevance
“…Neither did differences between countries in policy on colonoscopic surveillance interval impact colorectal cancer incidence in a previous PLSD study. 9 Notably, in the current study no colorectal, endometrial, ovarian, or urinary tract cancers were observed before 50 years of age in path_PMS2 carriers, giving even lower point estimates than have been reported previously. [6][7][8][11][12][13] We conclude that although path_PMS2 variants have been shown robustly to cause a rare recessively inherited cancer syndrome of childhood and adolescence termed constitutional mismatch repair deficiency (CMMRD) syndrome (https://www.omim.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Neither did differences between countries in policy on colonoscopic surveillance interval impact colorectal cancer incidence in a previous PLSD study. 9 Notably, in the current study no colorectal, endometrial, ovarian, or urinary tract cancers were observed before 50 years of age in path_PMS2 carriers, giving even lower point estimates than have been reported previously. [6][7][8][11][12][13] We conclude that although path_PMS2 variants have been shown robustly to cause a rare recessively inherited cancer syndrome of childhood and adolescence termed constitutional mismatch repair deficiency (CMMRD) syndrome (https://www.omim.…”
Section: Discussioncontrasting
confidence: 75%
“…Unexpected findings from previous studies have included path_MLH1 and path_MSH2 carriers appearing to have a lifetime risk of colorectal cancer (CRC) of approximately 50%, despite surveillance colonoscopy, [6][7][8] and that shorter intervals between colonoscopies do not seem to reduce the incidence of CRC in LS. 9,10 These findings challenge the assumptions that CRC in LS usually develops from a noninfiltrative adenoma precursor and that CRC can be prevented by colonoscopic detection and removal of adenomas in the colon and rectum. Additionally, previous studies in the Prospective Lynch Syndrome Database (PLSD) have shown no increase in cancer risk in path_PMS2 carriers before 40 years of age and, although observation years were limited in older path_PMS2 carriers, LS-associated cancers other than endometrial and prostate were not observed.…”
Section: Introductionmentioning
confidence: 93%
“…On a mechanistic level, this observation is very well compatible with recent evidence that mutant gain‐of‐function variants of TP53 are associated with the formation of flat lesions and an inflammatory phenotype favoring invasive growth in murine models . Clinically, our data support the existence of a distinct group of Lynch syndrome colorectal cancers that may manifest as interval cancers because they are not detectable even by high quality colonoscopy . Due to the limited number of tumors analyzed by panel sequencing, confirmation in independent tumor collections is strongly encouraged.…”
Section: Discussionsupporting
confidence: 88%
“…Recent prospective studies on CRC incidence in Lynch syndrome patients under colonoscopic surveillance show that colorectal cancers occurred despite regular colonoscopy with polypectomy . Based on this observation, Møller et al .…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this starts to explain recent findings that surveillance colonoscopy in LS patients only reduces CRC‐related mortality in LS by half, mostly by downstaging, whilst making no discernible impact on the rate at which LS‐CRCs occur – in complete contrast to the situation in the general population undergoing screening, where adenoma removal very significantly impacts on future CRC incidence . Significantly, individuals who have inherited mutations in both copies of the DNA repair genes MSH2 , MLH1 , MSH6 , PMS2 , MSH3 , and MUTYH can develop multiple colorectal adenomas, but patients with a mutation in only one copy of these genes do not.…”
Section: Molecular Heterogeneity Of Lynch Syndrome Tumoursmentioning
confidence: 97%